Sexual Harassment in Fitness Instructors: Prevalence, Perpetrators, and Mental Health Correlates - Mathisen, Therese Fostervold; Sølvberg, Nina; Sundgot-Borgen, Christine; Sundgot-Borgen, Jorunn (Frontiers in Psychiatry, 2021)
Introduction: This paper explores frequency of experiences of sexual harassment (SH) among fitness instructors, outlines the typical perpetrator, and explores associated mental health symptoms. Design: Cross-sectional survey. Materials and Methods: A total of 270 Norwegian fitness instructors, recruited in social media, responded to an electronic questionnaire in 2019/2020 on experiences of body appearance pressure, SH, and mental health symptoms. Outcomes included in this publication are experiences of SH, and symptoms of mental health issues based on the Hopkins symptom checklist, SCL-10; Beck Depression Inventory, BDI-1a; and Eating Disorder Examination Questionnaire, EDE-q. Results: The frequencies of SH experiences were 30% among 211 women and 22% among 59 men, respectively, with customers being the most frequent source of such approaches and personal trainers (PTs) more often reporting such experiences compared to group instructors (GIs) and to those operating as both PT and GI. Women having experienced SH had significantly higher scores in symptoms of depression, anxiety, and eating disorders compared to women with no such experience. Conclusion: The high frequency of SH experiences among fitness instructors, with customers emerging as perpetrators and typically in the context of personal training, necessitates increased awareness of SH in the fitness industry. To reduce the occurrence of SH, the fitness centers need to communicate countermeasures with high level of compliance.